1995
DOI: 10.1152/jappl.1995.79.4.1310
|View full text |Cite
|
Sign up to set email alerts
|

Responses of IGF-I to endogenous increases in growth hormone after heavy-resistance exercise

Abstract: The purpose of this study was to examine the effects of a heavy-resistance exercise protocol known to dramatically elevate immunoreactive growth hormone (GH) on circulating insulin-like growth factor I (IGF-I) after the exercise stimulus. Seven men (23.1 +/- 2.4 yr) volunteered to participate in this study. Each subject was asked to perform an eight-station heavy-resistance exercise protocol consisting of 3 sets of 10 repetition maximum resistances with 1-min rest between sets and exercises followed by a recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 22 publications
6
55
0
1
Order By: Relevance
“…The indisputable importance of the hippocampus in learning and memory and the role of BDNF in mediating hippocampal synaptic plasticity are well established [17][18][19][20]; while additional evidence indicates a role for insulin-like growth factor (IGF-1) in mediating the cognitive effects of exercise [21][22][23]. Interestingly, serum BDNF concentration has repeatedly been reported to increase following exercise in humans [9,[24][25][26] (for review see [27]), while IGF-1 responses to exercise are more variable [28][29][30].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The indisputable importance of the hippocampus in learning and memory and the role of BDNF in mediating hippocampal synaptic plasticity are well established [17][18][19][20]; while additional evidence indicates a role for insulin-like growth factor (IGF-1) in mediating the cognitive effects of exercise [21][22][23]. Interestingly, serum BDNF concentration has repeatedly been reported to increase following exercise in humans [9,[24][25][26] (for review see [27]), while IGF-1 responses to exercise are more variable [28][29][30].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In contrast to this view, Wallace et al demonstrated similar relative changes in serum levels of tIGF-I, IGFBP-3 and acid-labile subunit (ALS) during a 30-min bout of moderate exercise [5]. However, increased IGF-I concomitantly with unchanged IGFBP-3 has also been reported [22]. …”
Section: Acute Changes In Total Igf-i In Relation To a Bout Of Exercisementioning
confidence: 99%
“…The effects of exercise on the GH/IGF-I axis have been investigated. A large number of studies indicate that GH levels increase 10 minutes after the beginning of training and may increase up to 100-fold, especially in response to anaerobic exercise and hypoxia [24][25][26] . Daytime exercise has also been shown to increase GH secretion during sleep 27 .…”
Section: Gh Abusementioning
confidence: 99%
“…The physiological increase in GH levels seen in normal exercise makes it hard to differentiate this increase from that caused by external GH administration, as in doping situations. The reports of the effect of exercise upon IGF-I have also been conflicting, some of them showing no increase 26,29 , while in others 30,31 IGF-I was increased in a manner dependent on the exercise intensity.…”
Section: Gh Abusementioning
confidence: 99%